SIG DALAM PEMETAAN SEBARAN GURU IPS DAN GEOGRAFI DI WILAYAH KOTA METRO - Riki Tri Kurniawan; Budiyono Budiyono; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2015)
This research aimed to review the use of GIS in mapping the distribution of social studies and geography teacher at junior and senior high school on Metro Citys region in 2014. This research focused on map,GIS data and the distribution of social studies and Geographys teacher at Metro City. This research used descriptive informative method. The results in this study were proved that the data like facilities, teacher of junior and senior high school in Metro city can be presented through maps and GIS and the distribution and the need for social studies and Geographys teacher at the Metro City region is not spread evenly and infact, it encounter excess of social study and geography teacher and that data can be presented through the map.Penelitian ini bertujuan untuk mengkaji tentang pemanfaatan SIG dalam pemetaan sebaran guru IPS dan geografi pada SMP dan SMA Negeri Diwilayah Kota Metro tahun 2014. Titik tekan kajianya pada peta dan data SIG SMP dan SMA serta persebaran guru IPS Geografi di Kota Metro. Penelitian ini menggunakan metode deskriptif informatif. Hasil dalam penelitian ini adalah data fasilitas serta guru SMP dan SMA Negeri di Kota Metro dapat disajikan melalui peta dan SIG serta diketahui bahwa sebaran dan kebutuhan guru IPS Geografi di wilayah Kota Metro tidak merata bahkan mengalami kelebihan guru IPS Geografi dan keadaan tersebut dapat disajikan melalui peta.Kata Kunci: sistem informasi geografi, pemetaan, basisdata, kebutuhan guru.